Assessment of heavy-metal pollution in three different Indian water bodies by combination of multivariate analysis and water pollution indices. Issue 1 (2nd January 2020) - Kumar, Vinod; Sharma, Anket; Kumar, Rakesh; Bhardwaj, Renu; Kumar Thukral, Ashwani; Rodrigo-Comino, Jesús
Abstract: Water quality is a big concern for the humankind as it is the most important natural resource. However, the non-controlled growth of rural and urban areas in rapidly developed countries such as India is affecting water quality. In this research, we pretend to assess and demonstrate the heavy-metal status of three different water bodies of Indus, Beas and Sutlej Rivers and Harike Wetland. Data on water quality from 2013 to 2017 were analyzed through multivariate statistic techniques (cluster analysis – CA – and principal component analysis – PCA) and compared among them using public water pollution indexes. The results of CA and PCA showed that Sutlej River and Harike Wetland are included in the same group, whereas Beas River formed a separate one. This may be due to the high content of Pb, Cu, and Zn in these water bodies as compared with Beas River. The Pb content of all the water bodies exceeded the limit for EPR, BIS and WHO guidelines for drinking water. The heavy-metal pollution index was also applied to the contents of different heavy metals to find which water body is more polluted, and from their results, it was found that Harike Wetland and Sutlej River are critically polluted with heavy metals.